Evaluation of the Risk of Rabies in Human Victims through Implementation of Integrated Bite Case Management System in Phnom Penh, Cambodia. (March 2022) - Tazawa, K.; Lewis, A.N.; Ly, S.; Peng, Y.; Duong, V.; Lohr, F.; Gibson, A.D.; Phimpraphai, W.; Gamble, L.
Abstract : Purpose: This study aims to evaluate the implementation of a hospital-based integrated bite case management system (IBCM) in Phnom Penh to identify potential improvements and assess the risk of rabies in human victims to help guide animal health interventions and post-exposure treatment. Methods & Materials: The surveillance programme was initiated from human dog-bite patients presented to the Institute Pasteur du Cambodge (IPC) Vaccination Unit in Phnom Penh for post-exposure prophylactic treatment, or through public reports between October 2020 and June 2021. All identified individuals with knowledge of a biting dog were engaged during the investigation. The standardised questionnaires were administered by phone, or in-person where deemed necessary. Each case was assigned with a rabies status; rabid, probable, suspect/inconclusive, and non-case depending on the outcome of an investigation. Univariate logistic regression was performed with all inputs except for inconclusive cases to evaluate the risk factors in case demographics associated with rabid animals. Results: During the study period, 5, 035 investigations were conducted. The surveillance system detected 17 rabid cases associated with human dog-bite patients, and 2 cases through other reports. Fifty-seven cases were defined as probable, and 2, 745 biting dogs were considered not rabid at the time of the incidents. A definitive conclusion was not drawn in 2, 214 cases. The vaccination rate of known biting dogs was 18.6%. Univariate analyses showed that case demographics from the earliest stage of an investigation including animals showing signs of sickness (OR: 135.8, 95%CI: 42.0 – 439.3), animals' death described as spontaneous (OR: 111.2, 95%CI: 26.3 – 469.9), animals that were killed (OR: 126.3, 95%CI: 42.4 – 545.3), ownerless animals (OR: 33.5, 95%CI: 11.5 – 97.4), patients older than 15 years old (OR: 5.3, 95%CI: 1.5 – 18.9), and multiple bite victims in a case (OR: 6.8, 95%CI: 2.3 – 20.2) were associated with confirmed rabid cases. Conclusion: The study identified barriers to successful sample collection and thorough follow-up with patients which could impact on the system competency. The results of the study indicated that the initial case demographics could be used to assist not only prioritise cases for the IBCM investigation, but also spare PEP prescription for cases of low risk.